Investigating the ppp theory and long-run estimates for five Asian countries - Choji, Niri Martha; Sek, Siok Kun (International Journal of Engineering and Technology, 2018)
The theory of purchasing power parity (PPP) theory posits that the conversion rate between two currencies ought to be the same as the ratio of the total price levels between two currencies. Using monthly recent panel data for five Asian countries, from the period 1996M01-2016M08, the paper examined the PPP theory by utilizing robust methods of panel unit root and cointegration (Pesaran and Westerlund) tests that put into consideration cross-sectional dependence. The panel unit root test results show that all the variables considered are not stationary at levels but stationary at first difference (all variables are I(1)), because of that, the cointegration test was carried out. Results showed the presence of long-run relationship among the variables implying that the purchasing power parity theory exists in the long-run. Furthermore, the long-run relationships were estimated using the dynamic ordinary least squares (DOLS), fully modified ordinary least squares (FMOLS) and the mean group (MG) estimators. Surprisingly, all these estimators gave similar results, they showed that the domestic prices cause depreciation while the foreign prices cause appreciation of the nominal exchange rates in the five Asian countries. Generally, the effect of nominal exchange rate appreciation is more than depreciation in the five Asian countries.